2021
DOI: 10.21203/rs.3.rs-230129/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scraping and grazing herbivorous/detritivorous fish display opposite feeding behaviours under different protection regulations

Abstract: Background:Functional groups, especially herbivorous fishes, are important for mediating benthic community structure on coral reefs. Herbivorous and detritivorous fish display complex feeding behaviour, and research into schooling feeding behaviour and feeding rates, and how these change with environmental and social behavioural variables is lacking. Such knowledge is imperative to infer how herbivory/detritivory will change, in light of changing resources and communities, specifically whether reefs can recove… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Alternatively, observations made by other studies suggest that herbivorous fish abundances, in particular parrotfish family appeared to be more influenced by management status (Price et al, 2021), environmental conditions (McClanahan and Muthiga, 2020), and habitat characteristics (Vallès and Oxenford, 2014) rather than fishing effect. Similarly, density of surgeonfish species was influenced more by the changes to benthic composition than protection status (Russ et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Alternatively, observations made by other studies suggest that herbivorous fish abundances, in particular parrotfish family appeared to be more influenced by management status (Price et al, 2021), environmental conditions (McClanahan and Muthiga, 2020), and habitat characteristics (Vallès and Oxenford, 2014) rather than fishing effect. Similarly, density of surgeonfish species was influenced more by the changes to benthic composition than protection status (Russ et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…However, this study suggests that the increasing of abundance of rabbitfish family might be affected more by environmental factors as mentioned by (Olds et al, 2013;Roff et al, 2019) rather than predation or fishing effect. Price et al (2021) found that abundances of grazers and browsers increased in the fished areas with high algal cover. Personal observations suggest the presence of seagrass beds and/or mangroves close to fished reefs (particularly at Nabq), could be an important factor in determining the significance of Siganids associated with them.…”
Section: Discussionmentioning
confidence: 97%